Context-aware systems and applications First International Conference, ICCASA 2012, Ho Chi Minh City, Vietnam, November 26-27, 2012, revised selected papers - Hung, Nguyen Manh; Tung, Nguyen Thanh; Suzuki, Junichi (Lecture notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2013)
This book constitutes the thoroughly refereed proceedings of the first International Conference on Context-Aware Systems and Applications, ICCASA 2012, held in Ho Chi Minh City, Vietnam, in November 2012. The 34 revised full papers presented were carefully selected and reviewed from over 100 submissions. The papers cover a wide spectrum of issues in the area of Context-Aware Systems (CAS). CAS are going to shape networked computing systems of the future